A cyber-physical system for quality-oriented assembly of automotive electric motors. (January 2018) - Colledani, M.; Coupek, D.; Verl, A.; Aichele, J.; Yemane, A.
Abstract: The production of motors for the electric vehicles requires innovative and systematic quality control approaches to boost efficiency while moving from low volume towards mass production. In this context, end-of-line quality testing methods are usually applied to assess the product functionality at the end of the process chain. However, this approach does not allow process monitoring and the in-line prevention and correction of defects, leading to significant scrap rates and value losses. This paper presents a new system-level strategy for the in-line quality-oriented assembly of rotors in the production of automotive electric drives. The new strategy is based on a new cyber-physical system that optimizes the assembly strategy depending on the quality of magnetized stacks, monitored with data gathered by in-line inspection. For each batch, the magnetic stacks to be assembled and their orientation is selected according to an optimization algorithm, aiming at minimizing the deviation from the target total integral magnetic flux and maximizing the field uniformity in the magnetized rotor. The impact of the proposed strategy on the quality and productivity related performance measures are predicted by analytical methods. Experimental results based on an industrial case study are reported, showing that the application of the proposed strategy yields a significant increase in the production rate of conforming engines. The proposed approach paves the way to innovative zero-defect manufacturing strategies at system level in emerging, high-tech, manufacturing sectors.